Does Regulation of Physicians Reduce Health Care Spending?. (5th March 2017) - Barkowski, Scott
Abstract : The medical community argues that physician fear of legal liability increases health care spending. Theoretically, though, the effect could be positive or negative, and empirical evidence has supported both cases. Previous studies, however, have ignored the fact that physicians face risk from industry oversight groups like state‐level medical licensing boards in addition to civil litigation risk. This article addresses this omission by incorporating previously unused data on punishments by oversight groups against physicians, known as adverse actions, along with malpractice payments data to study state‐level health care spending. My analysis suggests that, contrary to conventional wisdom, spending does not rise in response to increased risk. An increase in adverse actions of 16 (the year‐to‐year average) is associated with statistically significant, annual decreases in state spending on hospital care of approximately 22 million, and on prescription drugs of nearly 10 million. Malpractice payments are estimated to have smaller, statistically insignificant effects.